Quantitative aspects of entanglement in the driven Jaynes-Cummings model - Marchiolli, Marcelo A. (Taylor & Francis Ltd, 2006)
Adopting the framework of the Jaynes-Cummings model with an external quantum field, we obtain exact analytical expressions of the normally ordered moments for any kind of cavity and driving fields. Such analytical results are expressed in the integral form, with their integrands having a commom term that describes the product of the Glauber-Sudarshan quasiprobability distribution functions for each field, and a kernel responsible for the entanglement. Considering a specific initial state of the tripartite system, the normally ordered moments are then applied to investigate not only the squeezing effect and the nonlocal correlation measure based on the total variance of a pair of Einstein-Podolsky-Rosen type operators for continuous variable systems, but also the Shchukin-Vogel criterion. This kind of numerical investigation constitutes the first quantitative characterization of the entanglement properties for the driven Jaynes-Cummings model.